2008
DOI: 10.2478/s11687-008-0034-z
|View full text |Cite
|
Sign up to set email alerts
|

A case of complicated cerebral toxocariasis in a 4-year old child

Abstract: SummaryWe report the case of a 4-year-old boy suffering from a cerebral form of toxocariasis. High serum titres of antiToxocara antibodies indicated that the primary infection was induced by a high number of Toxocara eggs and that the larvae did not penetrate to cerebrospinal fluid due to the hematoencephalic barrier. MRI of the patient´s brain showed multiple focal lesions spread diffusely in almost all parts of the brain, predominantly paraventricularly. These might be eosinophil-rich granulomatous infiltrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Encephalic localization has been reported in 34 patients [18 men (54.5%); mean age 33.5 ± 21.3 years]; 2 patients were classified as meningitis ( 38 , 52 ), 1 as encephalitis ( 37 ), 4 as meningoencephalitis ( 46 , 53 , 54 , 58 ), 3 as encephalomyelitis ( 29 , 49 , 51 ), 1 as meningoencephalomyelitis( 55 ), 2 as cerebral abscess ( 41 , 50 ), and 1 as obstructive hydrocephalus ( 61 ). Thirteen were generically defined as cerebral toxocariasis ( 21 , 39 , 40 , 42 – 45 , 47 , 48 , 56 , 57 , 59 , 60 ) and seven were classified as vasculitis ( 62 68 ).…”
Section: Clinical and Mri Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Encephalic localization has been reported in 34 patients [18 men (54.5%); mean age 33.5 ± 21.3 years]; 2 patients were classified as meningitis ( 38 , 52 ), 1 as encephalitis ( 37 ), 4 as meningoencephalitis ( 46 , 53 , 54 , 58 ), 3 as encephalomyelitis ( 29 , 49 , 51 ), 1 as meningoencephalomyelitis( 55 ), 2 as cerebral abscess ( 41 , 50 ), and 1 as obstructive hydrocephalus ( 61 ). Thirteen were generically defined as cerebral toxocariasis ( 21 , 39 , 40 , 42 – 45 , 47 , 48 , 56 , 57 , 59 , 60 ) and seven were classified as vasculitis ( 62 68 ).…”
Section: Clinical and Mri Findingsmentioning
confidence: 99%
“…Out of the 19 patients assessed by CSF ELISA, 15 tested positive of whom three were also confirmed by positive WB; in two additional patients, the presence of anti- Toxocara antibodies was detected only by WB. In 10 patients, of whom 4 were vasculitis ( 62 , 63 , 67 , 68 ), in which the diagnosis of neurotoxocariosis was based only on the presence of a positive serum ELISA seropositivity [CSF ELISA was negative in 5 ( 39 , 47 , 48 , 59 , 63 ) and not performed in the other 5 ( 53 , 56 , 62 , 67 , 68 )], not confirmed by biopsy or WB (Table 1 ; Table S1 in Supplementary Material).…”
Section: Clinical and Mri Findingsmentioning
confidence: 99%
“…Toxocara spp. infestations present with a wide spectrum of symptoms from general inflammation of internal organs (VLM) with formation of the eosinophilic granulomas through ocular or brain involvement to an asymptomatic form that is defined as the accidental detection of eosinophilia and specific antibodies . The clinical form of disease depends on the intensity of the infestation, the localization of the larvae, the age of the host, the efficiency of the immune system and the reinfection history .…”
Section: Introductionmentioning
confidence: 99%
“…Helminths often belong among the opportune pathogens that attack the organisms of patients with serious respiratory disease (Shuji et al, 2006). Königová et al (2010) found in paediatric patients at the age of 9 months up to 16 years with acute or chronic respiratory and gastrointestinal infection the occurrence of A. lumbricoides and T. trichuria. The highest intensity of infection was in the children at the age of 3-5 years living in bad hygienic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The high levels of total IgE antibodies connected with ascariosis limit the evidence supporting of this test in diagnostics of allergy. The diagnostic significance at some tissue helminthoses at the syndrome larva migrans, or others is also ascribed to the changes in the value of C-reactive protein (Kinčeková et al, 2008). Several studies have dealt with the serum concentration of IgE in the patients infected with helminths or protozoa.…”
Section: Reference Valuesmentioning
confidence: 99%